Sex identification based on lipprint patterns: A Review - Fiqna Amalya; Devi A. A. Nasution; Myrtati D. Artaria; Yao-Fong Chen (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Many researchers have conducted studies oflip prints to aid in human identification. Thedistinctiveness of the lip print pattern will be a distinguishing feature from one person to the next.Purpose: This study analyzes the dominant types and patterns of lips print in males and females.Results: Most males--7 research out of 20--were type III lip print pattern, and 6 out of 20 belong to the type II lipprint pattern. Femalesmainly were typed II pattern—11 out of 20, and type I pattern—7 out of 20.Conclusion: When the patterns are type I or type III, the sex of the individual can be easily identified; however,when the pattern is type II, the individual could be either a male or a female, with a higher probability of being afemale. Other forms of identification should be available to support sex identification in this circumstance.